Experimental Study on Lightweight Precast Composite Slab of High-Titanium Heavy-Slag Concrete - Jinkun Sun; Rita Yi Man Li; Nuttapong Jotikasthira; Kui Li; Liyun Zeng (Advances in Civil Engineering)
Precast composite slabs are an essential component in concrete-prefabricated buildings. At present, there are problems such as overweightedness and imperfect test for quality and structural performance of the precast floors, leading to restriction in the development of prefabricated buildings. In this study, by using industrial solid-waste high-titanium heavy slag as coarse and fine aggregates, with fly ash and silica fume for the partial substitution of the cement, we developed a green lightweight precast composite slab of high-titanium heavy-slag concrete (LPCSHTHSC) after adding shale ceramite as the light aggregate. By selecting the weight and the strength of LPCSHTHSC as the technical control indexes, we performed an orthogonal test of lightweight proportions. Through a comprehensive analysis of the compressive strength, splitting tensile strength, density, and an economic consideration, the optimal proportion was determined as follows: water-to-binder ratio of 0.43, mixing amount of the fly ash of 4%, mixing amount of the silica fume of 8%, mixing amount of the water-reducing agent of 0.5%, sand ratio of 35%, and cement at the strength grade of 42.5. Next, the bending performance test was conducted on LPCSHTHSC. According to the results, the LPCSHTHSC exhibited excellent mechanical performance, and its ultimate bearing capacity far exceeded the designed value. The ultimate bearing capacity calculated using the plastic hinge wire method differed slightly from the test value, suggesting the applicability of the proposed method to the calculation of the ultimate bearing capacity. Finally, the finite element analysis results of LPCSHTHSC were consistent with the actual bending mechanical performance test results, which proved both the accuracy and the reliability of the present finite element analysis based on the plastic damage constitutive model. The present study can provide an insightful theoretical and test foundation for the lightweight application of high-titanium heavy-slag concrete in other prefabricated components.